Ovarian cancer among 8005 women from a breast cancer family history clinic: no increased risk of invasive ovarian cancer in families testing negative for BRCA1 and BRCA2. Issue 6 (28th March 2013) - Ingham, Sarah Louise; Warwick, Jane; Buchan, Iain; Sahin, Sarah; O'Hara, Catherine; Moran, Anthony; Howell, Anthony; Evans, D Gareth
Abstract : Background: Mutations in BRCA1/2 genes confer ovarian, alongside breast, cancer risk. We examined the risk of developing ovarian cancer in BRCA1/2 -positive families and if this risk is extended to BRCA negative families. Patients and Methods: A prospective study involving women seen at a single family history clinic in Manchester, UK. Patients were excluded if they had ovarian cancer or oophorectomy prior to clinic. Follow-up was censored at the latest date of: 31/12/2010; ovarian cancer diagnosis; oophorectomy; or death. We used person-years at risk to assess ovarian cancer rates in the study population, subdivided by genetic status ( BRCA1, BRCA2, BRCA negative, BRCA untested) compared with the general population. Results: We studied 8005 women from 895 families. Women from BRCA2 mutation families showed a 17-fold increased risk of invasive ovarian cancer (relative risk (RR) 16.67; 95% CI 5.41 to 38.89). This risk increased to 50-fold in women from families with BRCA1 mutations (RR 50.00; 95% CI 26.62 to 85.50). No association was found for women in families tested negative for BRCA1/2, where there was 1 observed invasive ovarian cancer in 1613 women when 2.74 were expected (RR 0.37; 95% CI 0.01 to 2.03). There was no association with ovarian cancer in families untested for BRCA1/2 (RR 0.99; 95% CI 0.45 to 1.88). Discussion: This study showed no increased risk of ovarian cancer in families that tested negative for BRCA1/2 or were untested. These data help counselling women from BRCA1/2 negative families with breast cancer that their risk of invasive ovarian cancer is not higher than the general population.